Hubungan Harga Diri dan Optimisme dengan Kesejahteraan Subjektif pada Mahasiswa Magister Psikologi Universitas Medan Area - Nur Afni Safarina; Abdul Munir; Nuraini Nuraini (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2019)
The aim of this study was to determine and analyze the relationship of self-esteem and optimism with subjective well-being of UMA Master of Psychology students. The approad of this study was correlational quantitative method. The samples of this study were 75 UMA psychology masters who are still active taken by simple random sampling technique. Data collection methods in this study used three scales, namely the scale of subjective wellbeing, self-esteem scale and optimism scale. Data were analyzed with Multiple Regression Analysis technique. The results of this study indicate (1) there is a significant positive relationship between self-esteem and optimism with subjective well-being, where the coefficient rx12y = 0.640 and p = 0,000 with contribution of 40.9%. (2) there is a significant positive relationship between self-esteem and subjective well-being, where coefficient rx1y = 0.635 and p = 0,000, contribution of 40.3%. (3) there is a significant positive relationship between optimism and subjective wellbeing, where the coefficient rx2y = 0.414 and p = 0,000, with a contribution of 17.1%, thus stated that all hypotheses are acceptable.